The Effect of Service Quality, Emotional Marketing and Brand Image on Satisfaction - Hardiman Hardiman; Kristina Anindita Hayuningtias (Universitas Muhammadiyah Makassar, 2023)
This study aims to test the effect of service quality, emotional marketing and brand image on consumer satisfaction. This study used non-probability sampling and purposive sampling techniques as sampling techniques. Data collection in this study was through google form and obtained as many as 138 respondents. The technical analysis used is multiple liner regression analysis. The results of this study show that the variables of service quality, emotional marketing and brand image have a positive and significant effect on consumer satisfaction, so it can be concluded that the better the quality of service, emotional marketing and brand image in the eyes of customers, the more satisfied consumers will be